1999
DOI: 10.1139/g98-148
|View full text |Cite
|
Sign up to set email alerts
|

Generation and chromosome mapping of expressed sequence tags (ESTs) from a human infant thymus

Abstract: In an effort to identify novel genes that are expressed differentially in an infant thymus, we constructed an oligo-d(T) primed cDNA library from a human infant thymus followed by single-run partial sequencing to generate expressed sequence tags (ESTs). Characterization of more than 1400 sequences enabled us to convert human thymus transcripts into 1223 useful ESTs. These ESTs consisted of 613 (50.1%) showing homology to known human genes, 51 (4.2%) matching to genes from other species, 289 (23.6%) matching ES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Comparison of the FTY gene expression pattern with that of the human infant thymus ( 3 ) showed that the general expression profile of these two tissues is very similar. The higher representation of the cell division and gene expression groups in FTY than in the human infant might be related to the earlier developmental stage of FTY.…”
Section: Resultsmentioning
confidence: 98%
“…Comparison of the FTY gene expression pattern with that of the human infant thymus ( 3 ) showed that the general expression profile of these two tissues is very similar. The higher representation of the cell division and gene expression groups in FTY than in the human infant might be related to the earlier developmental stage of FTY.…”
Section: Resultsmentioning
confidence: 98%